PENGARUH POLA DAN PANJANG DATA HUJAN TERHADAP DESAIN PENAMPUNGAN AIR HUJAN PADA TIGA STASIUN HUJAN DI INDONESIA - Budirahardjo, Elly Kusumawati (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Rainwater Harvesting (RWH) is an alternative water supply system to meet household water demands independently. Rainfall is one of input parameters for RWH design by assuming that evaporation is neglected. This study examines the influence of different rainfall patterns on RWH reservoir’s sizing from 3 different rainfall stations in Indonesia. In order to get reliable reservoir design, RWH simulation required long rainfall time series data. However, numbers of rainfall station with long time series data are limited, so the possibility of using shorter rainfall data in the design is examined in this study as well. The effect of rainfall patterns to RWH is analyzed by comparing their reservoir volume. The optimum reservoir is obtained by optimizing time reliability parameters. The length of time series data is analyzed by finding similarities between water savings that simulated with long-term and short-term data series. It can be concluded that rainfall characteristics, namely intensity and number of rainy days, affects RWH reservoir’s size. Equatorial and Local rain patterns require smaller reservoir volume than the Monsoon. Short-term series of rainfall data possible to use for designing RWH. The recommended length of time series data is 15 years for Equatorial type, 13 years for Monsoon type and 9 years for Local type. The results of sensitivity analysis show that RWH performance, represent by reservoir reliability parameter, is not sensitive to its input parameters.Keywords: rainwater harvesting; rainfall pattern; time series; storage performance